Early‐ and late‐onset selective fetal growth restriction in monochorionic diamniotic twin pregnancy: natural history and diagnostic criteria. (3rd April 2020) - Curado, J.; Sileo, F.; Bhide, A.; Thilaganathan, B.; Khalil, A.
ABSTRACT: Objectives: To evaluate the natural history and outcome of selective fetal growth restriction (sFGR) in monochorionic diamniotic (MCDA) twin pregnancy, according to gestational age at onset and various reported diagnostic criteria, and to quantify the risk of superimposed twin‐to‐twin transfusion syndrome (TTTS). Methods: This was a cohort study of MCDA twin pregnancies that had their routine antenatal care from the first trimester at St George's Hospital, London, UK. Pregnancies had ultrasound examinations every 2 weeks at 16–24 weeks and then every 2–3 weeks until delivery. The diagnostic criteria for sFGR were estimated fetal weight (EFW) of one twin < 10 th centile and intertwin EFW discordance ≥ 25%. We also applied other diagnostic criteria reported in a recent Delphi consensus. Pregnancies in which the diagnosis of TTTS was made before that of sFGR were not included in the analysis. Pregnancies that underwent fetal intervention for sFGR were excluded. The incidence of sFGR was compared between the different diagnostic criteria, overall and according to gestational age at onset. In all subsequent analyses, cases of sFGR included those diagnosed according to any of the criteria. The Gratacós classification of sFGR was applied (Type I, II or III). Pregnancy outcomes included miscarriage, intrauterine death, neonatal death and admission to the neonatal unit. Comparisons between groups were carried out using the Mann–Whitney U ‐test for continuous variables and the chi‐square or Fisher's exact test for categorical variables. Results: The analysis included 287 MCDA twin pregnancies. According to the International Society of Ultrasound in Obstetrics and Gynecology diagnostic criteria, the incidence of early (< 24 weeks) sFGR was 4.9%, while that of late sFGR was 3.8%. When applying the various diagnostic criteria, the incidence of early sFGR varied from 1.7% to 9.1% and that of late sFGR varied from 1.1% to 5.9%. In early‐onset cases, the incidence of Type I sFGR was 80.8%, that of Type II was 15.4% and that of Type III was 3.8%. The corresponding figures in late‐onset cases were 94.4%, 5.6% and 0%. The incidence of superimposed TTTS was 26.9% in cases affected by early‐onset sFGR and 5.6% in those affected by late‐onset sFGR. The incidence of perinatal death was 8.0% in early‐onset sFGR and 5.6% in late‐onset sFGR ( P  = 0.661). Admission to the neonatal unit occurred in 61.0% and 52.9% of cases, respectively ( P  = 0.484). Conclusions: In MCDA twin pregnancies, early‐onset sFGR is slightly more common than is late‐onset sFGR, although this difference was not significant, and is associated with worse perinatal outcome. The incidence of Types II and III sFGR is higher in early‐onset sFGR. The incidence also varies according to the diagnostic criteria used, which supports the use of standardized international diagnostic criteria. Superimposed TTTS is more common in early‐ than in late‐onset sFGR. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.